An additive manufacturing process model for product family design. Issue 11 (1st November 2016) - Lei, Ningrong; Yao, Xiling; Moon, Seung Ki; Bi, Guijun
ABSTRACT: Additive manufacturing (AM) is projected to have a profound impact on mass customisation. In order to benefit from this new technology, we need to incorporate AM into design processes. This paper addresses that need by introducing an AM process model for product family design. The proposed model reflects the ability of AM to produce customised and complex parts without tooling efforts. By utilising AM, we eliminate all constraints which arise in conventional product family designs from finding a compromise between commonality and performance. The proposed model starts by identifying design requirements and constraints. Subsequently, we use topology optimisation to determine an optimal design for each product. Next, finite element analysis and cost analysis are performed. We combine the analysis results in one three-dimensional plot, which displays the merits of the individual component realisations. Thus, a fair and competitive component evaluation is possible and the most suitable product family design can be selected. The final designs are fabricated using fused desposition modelling. A case study is conducted to illustrate how the proposed model facilitates the benefits of AM. The results show that the proposed model has the potential to provide affordable customisation.